BBX19 Interacts with CONSTANS to Repress FLOWERING LOCUS T Transcription, Defining a Flowering Time Checkpoint in Arabidopsis . Issue 9 (16th September 2014) - Wang, Chang-Quan; Guthrie, Cade; Sarmast, Mostafa Khoshhal; Dehesh, Katayoon
Abstract : BBX19, a transcription factor with two B-Box motifs, is a clock output component that functions as a flowering time checkpoint by physically interacting with CO and depleting the CO pool required for FT activation. The integrity of the Box1 motif is necessary for the functionality of BBX19. Abstract: The timely transition of vegetative to reproductive development is coordinated through quantitative regulation of floral pathway genes in response to physiological and environmental cues. Here, we show that the circadian-controlled expression of the Arabidopsis thaliana floral transition regulators FLOWERING LOCUS T ( FT ) and CONSTANS ( CO ) is antiphasic to that of BBX19, a transcription factor with two B-Box motifs. Diminished expression of BBX19 by RNA interference accelerates flowering, and constitutive expression of BBX19 delays flowering under inductive photoperiods. This delay is not accompanied by the alteration of CO expression levels but rather by a reduction of transcript levels of FT and the FT-regulated genes SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1, LEAFY, and FRUITFUL . Similar to CO, BBX19 is expressed in vasculature. BBX19 and CO colocalize in the nucleus and interact physically in vivo. In transient assays, coinfiltration of 10-fold more CO overcomes the BBX19-mediated repression of FT activation. Substitution of the conserved Cys-25 to Ser in the BBX19 Box1 motif abolishes the BBX19–CO interaction and eliminates the negative regulation of flowering time, while the analogous C76S substitution in the Box2 motif is ineffective. Together, these results implicate BBX19 as a circadian clock output that depletes the active CO pool to accurately monitor daylength and precisely time FT expression.